Towards scalability improvements of HybriD-GM quantum simulator - Coelho, João Vítor Venceslau; de Ávila, Anderson Braga; de Souza, Samuel Xavier; Reiser, Renata Hax Sander (Anais do Workshop-Escola de Informática Teórica (WEIT); 2023: Anais do VII Workshop-Escola de Informática TeóricaDO - 10.5753/weit.2023.26608, 2023)
Currently quantum computers require specialized hardware to be used, until they become more feasibly the testing of quantum algorithms is done by simulation, which is a task of high temporal and spacial complexity. To address this issue, the HybriD-GM simulator, and many others around the world, are under research and improvement, this paper is an ongoing work on improvements for the multi-core support of the HybriD-GM simulator, the experiments are done with the Shor and Grover algorithms, while varying the number of cores and qubits for each, to improve the scalability the removal of critical regions by the usage of tasks and other OpenMP resources is exploited, and the study about the impact of others variables on the simulator is already planned, as well improvements for future works on the GPU, and GPU-CPU approaches and expansion to distributed computing for horizontal scalability of the system.